Othello - Dickins, Rosie; Unzner-Fischer, Christa Shakespeare, William (Usborne London, 2014)
William Shakespeare's tragic play about the Moor of Venice, fully illustrated and retold for younger readers. Part of the Usborne Reading Programme, this book is written for fully confident readers who still need to gain the stamina needed for standard length books. Perfect for children who can read fluidly but are still gaining confidence